Betrayed - Scottoline, Lisa (2014)
"Judy has always championed the underdog, so when Iris, the housekeeper and best friend of Judy's beloved Aunt Barb, is found dead of an apparent heart attack, Judy begins to suspect foul play. The circumstances of the death leave Judy with more questions than answers, and never before has murder struck so close to home."--
Keywords: Rosato & Associates (Imaginary organization) -- Fiction; Legal stories; Mystery fiction